2014
DOI: 10.1155/2014/274303
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fear of Childbirth and Women’s Knowledge about Painless Childbirth

Abstract: This study investigated the association between fear of childbirth (FOC) and women's knowledge about painless childbirth methods. The study was performed on 900 multiparous women within the last month of pregnancy. Data was obtained through a questionnaire including the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) Turkish form A. FOC was defined as W-DEQ sum score ≥85. Women were questioned about their knowledge about painless childbirth and the most important source of this knowledge. Group 1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 23 publications
2
45
0
2
Order By: Relevance
“…A study from South Africa showed that women gained knowledge of pain relief from previous experience or from friends and relatives [14]. Similar results indicating the major source of information being from their friends and relatives were found in earlier studies too [15,16]. In contrary, a study done in Northern Nigeria showed the majority of women have heard of pain relief mostly from their caregivers and during the current pregnancy [12].…”
Section: Discussionsupporting
confidence: 62%
“…A study from South Africa showed that women gained knowledge of pain relief from previous experience or from friends and relatives [14]. Similar results indicating the major source of information being from their friends and relatives were found in earlier studies too [15,16]. In contrary, a study done in Northern Nigeria showed the majority of women have heard of pain relief mostly from their caregivers and during the current pregnancy [12].…”
Section: Discussionsupporting
confidence: 62%
“…In another study, the results showed that a negative birth outcome in the previous pregnancy, fear of childbirth during pregnancy, cesarean section, and nulliparity were the factors that most related to fear of childbirth (Nilsson et al, 2012). A study of 376 women by Aksoy et al showed that an extreme fear of childbirth is a factor linked to an increased rate of cesarean section (OR 4.22, 95% CI: 2.91-6.11) (Aksoy et al, 2014). A qualitative study conducted by Faisal et al in Iran on 14 nulliparous women who requested elective cesarean section without any medical reason showed that the main reasons for requesting cesarean section were extreme fear of childbirth, complications after normal vaginal delivery, and sexual dysfunction (Faisal et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Poliklinik kontrolü için hastaneye başvuran gebelere doğumun başlangıç belirtileri, doğum başladığında karışılabilecek durumlar, doğumhane ortamı, doğum masasında geçecek olan süre, doğum sırasında kullanılacak nefes egzersizleri, epizyotomi konusunda hemşireler tarafından verilen eğitimin kadınların yaşadığı doğum korkusu seviyesini azalttığı belirlenmiştir (39)(40)(41). Bununla birlikte, doğuma ilişkin gebelere verilen geleneksel eğitimin annelerde istenilen ruhsal iyileşmeyi sağlamada yeterli olmadığını savunan çalışmalar da bulunmaktadır (41).…”
Section: Discussionunclassified